Improving the production and managerial performance of tempeh chip MSMEs - Setiawan, Ferry; Wicaksono, Dhimas; Rizki, Ikbal; Hillal, Raden Fatchul; Widagdo, Djoko; Mahendra, Dimas Aditya (University of Islam Malang, 2024)
The Community Service Program of STTKD Lecturers is funded by the Directorate of Research and Community Service of the Ministry of Education and Culture due to the problems faced by Micro, Small, and Medium Enterprises (MSMEs) of tempeh chips brand